2022
DOI: 10.3390/antibiotics11111651
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Distribution of Virulent Multidrug-Resistant Staphylococcus aureus in Livestock, Environment, and Dairy Products

Abstract: Staphylococcus aureus is one of the most common causes of mastitis, leading to severe economic losses in the dairy industry. It is also zoonotic, with potential risks to public health. This study aimed to detect the occurrence of S. aureus-resistant strains isolated from cattle, buffalo, their environment, milk and dairy products; and to investigate the extent of animal, ecological, and food contamination by methicillin-resistant (MRSA) or enterotoxigenic S. aureus. Samples (n = 350) were collected from four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
1
11
2
Order By: Relevance
“…Continued research on the antibiotic resistance of pathogenic bacteria that infect fish is needed because it is essential for controlling the occurrence of multidrug-resistant bacteria and for the selection of appropriate therapeutic agents. The high percentage of MDR S. aureus in the current study is slightly higher than in a previous study conducted in Egypt (Badawy et al, 2022) where 83.3% of S. aureus isolates were MDR.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Continued research on the antibiotic resistance of pathogenic bacteria that infect fish is needed because it is essential for controlling the occurrence of multidrug-resistant bacteria and for the selection of appropriate therapeutic agents. The high percentage of MDR S. aureus in the current study is slightly higher than in a previous study conducted in Egypt (Badawy et al, 2022) where 83.3% of S. aureus isolates were MDR.…”
Section: Discussioncontrasting
confidence: 86%
“…S. aureus has been reported in fish and fishery products (Vaiyapuri et al, 2019). S. aureus is not a natural microbiota of fish and therefore its presence in fish is associated with unhygienic handling by fish handlers, processors or sellers, cross-contamination during transport and storage, and contamination by workers, due to the presence of this pathogen in the microbiome of most humans (Saito et al, 2011;Hammad et al, 2012;Sergelidis et al, 2014;Badawy et al, 2022). Proteus mirabilis is a Gram-negative, rod-shaped bacterium found in the environment, animal microbiota and humans (Drzewiecka, 2016), and an important zoonotic pathogen that causes infections in animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in these studies, most L. monocytogenes as well as strains of other Listeria spp., were found to be susceptible to a wide range of antimicrobials and there was no increase in antimicrobial resistance genes except for cephalosporin, fosfomycin, lincosamide and tetracycline resistance genes. Despite the few occurrences of antimicrobial resistance genes among the examined L. innocua isolates, which is considered a good sign for infection treatment, the spread of antimicrobial resistance among different bacterial species remains a major problem in Egyptian dairy farms ( Tartor et al, 2021 ; Badawy et al, 2022 ). Further studies on larger sets would be helpful to determine the state of antimicrobial resistance in Listeria from milk and dairy products, since high antimicrobial resistances among different bacterial species from dairy farms in Egypt prevail.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring the safety of food products, especially those consumed daily like milk and cheese, is paramount. Contamination of these dairy products with S. aureus can lead to foodborne illnesses, ranging from mild gastrointestinal discomfort to severe infections (Badawy et al, 2022;Sayed-Ahmed et al, 2020). The zoonotic S. aureus is of public health significance (Odetokun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such extensively drug-resistant (XDR) strains are especially difficult to treat and are associated with poor clinical outcomes. Other studies have also identified multidrug-resistant S. aureus strains from milk and other dairy products and this portends a serious risk to animal and human health (Oloso et al, 2018;Oludairo et al, 2020;Sayed-Ahmed et al, 2020;Tibebu et al, 2021;Badawy et al, 2022;Murray et al, 2022;Alembo & Torka, 2023;Gaddafi et al, 2023). The multidrug resistance patterns expressed by the S. aureus isolates suggest a broader resistance profile, encompassing multiple antibiotic classes, which further complicates treatment options.…”
mentioning
confidence: 99%